1989
DOI: 10.1056/nejm198912283212605
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Treatment with Recombinant Human Growth Hormone on Body Composition and Metabolism in Adults with Growth Hormone Deficiency

Abstract: In a double-blind, placebo-controlled trial, we studied the effects of six months of growth hormone replacement in 24 adults with growth hormone deficiency. Most of the patients had acquired growth hormone deficiency during adulthood as a consequence of treatment for pituitary tumors, and all were receiving appropriate thyroid, adrenal, and gonadal hormone replacement. The daily dose of recombinant human growth hormone (rhGH) was 0.07 U per kilogram of body weight, given subcutaneously at bedtime. The mean (+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

64
771
8
27

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,292 publications
(870 citation statements)
references
References 31 publications
64
771
8
27
Order By: Relevance
“…20,32 Besides, it was suggested that estrogen may attenuate growth hormone (GH) signaling 33 and GH was reported to increase lipid oxidation 34 and reduce body fatness. 35 In sum, estrogen can affect obesity phenotypes through different pathways which may interact with each other, and much work is needed to understand its precise role in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…20,32 Besides, it was suggested that estrogen may attenuate growth hormone (GH) signaling 33 and GH was reported to increase lipid oxidation 34 and reduce body fatness. 35 In sum, estrogen can affect obesity phenotypes through different pathways which may interact with each other, and much work is needed to understand its precise role in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This can also occur after irradiation or surgery of this region 6,10 ' 12 ' 17 ' 21 " 23 . Although there is no consensus of which would be the best method to detect GHd in adults 6,7,12 * 21 , Hoffman et al 12 have demonstrated that the ITT is extremely accurate in differentiating subjects with organic GHd from normal matched subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Muitos de seus efeitos no osso são mediados por IGF-1. O GH estimula a hidroxilação renal da 25-OH vit D3, absorção renal de cálcio e tem efeitos renais de retenção de fosfato (2,43). Outro provável mecanismo de ação do GH é através de aumento na carga mecânica imposta aos ossos, visto que o GH leva a maior massa e força muscular (5,44).…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified
“…A maioria dos estudos relata discreto declínio nos níveis séricos de T4 e elevação de T3 causada pelo aumento da conversão periférica do T4 para T3 (2,55). Neste estudo não encontramos mudanças significativas nos níveis de hormônios tireoideanos durante a reposição de GH.…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified
See 1 more Smart Citation